Analysis of Liver Histology and Severity of Metabolic Syndrome in Patients Suffering from Non-alcoholic Fatty Liver Disease (Medical Forum Monthly, 2024)
Objective: To analyze liver histology and severity of metabolic syndrome in patients suffering from nonalcoholic fatty liver disease.Study Design: Comparative study.Place and Duration of Study: This study was conducted at the Idris Teaching Hospital of Sialkot Medical College, Sialkot and Lahore General Hospital, Lahore from January 2018 to December 2018Materials and Methods: This is a comparative analysis in which we explored specific relationships between hepatic histology and markers of the metabolic syndrome. There were total 50 patients included in this study. The diagnosis was based on the histological presence of macrovesicularsteatosis, with or without lobular inflammation, hepatocellular degeneration, or fibrosis. Results: In this study the data was collected from 50 patients with biopsy-proven NAFLD, a relationship between the severity of the metabolic syndrome and NAFLD was observed. While measures of adiposity correlated with hepatic steatosis, hepatic inflammation and fibrosis were associated with the presence and severity of the metabolic syndrome. This finding has clinical implications, since hepatic ultrasound and serum transaminases have limited utility in predicting hepatic inflammation and fibrosis and there is current reliance on liver biopsies to confirm the diagnosis and indicate prognosis.Conclusion: It is concluded that NAFLD is associated with a high prevalence of obesity. There was a trend towards an association between NASH and metabolic syndrome, in addition patients with NAFLD with MetS were more likely to have severe steatosis and portal inflammation on liver biopsy.